Audiometric Outcomes in Chronic Otitis Media with Mastoid Involvement: A Five-Year Clinical Overview - Cristina Popescu; Renata Maria Văruț; Mihaela Popescu; Alin Iulian Silviu Popescu; Cristina Elena Singer (Diagnostics)
Background/Objectives. Otomastoiditis, an inflammatory condition affecting the middle ear and mastoid cells, poses significant risks for hearing impairment. This study aimed to analyze the clinical presentations, anatomical variations, and audiometric outcomes associated with acute and chronic otomastoiditis over a five-year period at the ENT Clinic of the Clinical County Emergency Hospital of Craiova. Methods. A retrospective clinical–statistical analysis was conducted on 145 patients aged 2 to 78 years, who were treated for otomastoiditis. The study involved a comprehensive review of clinical and audiometric data, with a focus on the type of hearing loss (conductive or mixed), audiometric thresholds, and the relationship between the anatomical form of the disease and the severity of hearing loss. Results. The majority of cases (93.83%) were chronic otomastoiditis, with 66.89% of patients presenting with mixed hearing loss and 33.10% with conductive hearing loss. Audiometric assessments revealed significant air conduction deficits, particularly at low and mid-range frequencies, with losses averaging 50–55 dB in cases of conductive hearing loss. Chronic cases demonstrated notable bone conduction impairments, indicating progressive cochlear damage. Statistical analysis identified a moderate correlation between the anatomical form of the disease and the severity of hearing loss, particularly in patients with cholesteatomatous-suppurative forms. Conclusions. This study underlines the critical need for the early and precise diagnosis of otomastoiditis, supported by audiometric evaluations. Our findings emphasize the substantial risk of progressive cochlear damage in chronic cases, underscoring the necessity for timely intervention to mitigate long-term hearing loss. These results offer valuable insights for clinicians, potentially guiding improved therapeutic approaches and contributing to enhanced patient outcomes in managing chronic otomastoiditis.